Site-specific DNA binding by the bacteriophage SP01-encoded type II DNA-binding protein. - Greene, J R (1985)
The bacteriophage SP01 genome encodes a virus-specific type II DNA-binding protein, TF1. The bacterial proteins of this ubiquitous and evolutionarily conserved class are thought to bind non-specifically to DNA. In contrast, the experiments described here demonstrate that TF1 binds to specific sites in SP01 DNA. Several of these sites have been characterized by DNase I 'footprinting' and four of them have been shown to overlap strong phage promoters for Bacillus subtilis RNA polymerase holoenzyme. We speculate on the possible structural basis of site-selective DNA binding by a protein of this class.